N-acetyl-L-cysteine protects against inhaled sulfur mustard poisoning in the large swine. (May 2013) - Jugg, B.; Fairhall, S.; Smith, A.; Rutter, S.; Mann, T.; Perrott, R.; Jenner, J.; Salguero, J.; Shute, J.; Sciuto, A. M.
<x xml:space="preserve">Abstract</x> Context. Sulfur mustard is a blister agent that can cause death by pulmonary damage. There is currently no effective treatment. N-acetyl-L-cysteine (NAC) has mucolytic and antioxidant actions and is an important pre-cursor of cellular glutathione synthesis. These actions may have potential to reduce mustard-induced lung injury. Objective. Evaluate the effect of nebulised NAC as a post-exposure treatment for inhaled sulfur mustard in a large animal model. Materials and methods. Fourteen anesthetized, surgically prepared pigs were exposed to sulfur mustard vapor (100 μg.kg− 1, 10 min) and monitored, spontaneously breathing, to 12 h. Control animals had no further intervention (n = 6). Animals in the treatment group were administered multiple inhaled doses of NAC (1 ml of 200 mg.ml− 1 Mucomyst™ at + 30 min, 2, 4, 6, 8, and 10 h post-exposure, n = 8). Cardiovascular and respiratory parameters were recorded. Arterial blood was collected for blood gas analysis while blood and bronchoalveolar lavage fluid were collected for hematology and inflammatory cell analysis. Urine was collected to detect a sulfur mustard breakdown product. Lung tissue samples were taken for histopathological and post-experimental analyses. Results. Five of six sulfur mustard-exposed animals survived to 12 h. Arterial blood oxygenation (PaO2) and saturation levels were significantly decreased at 12 h. Arterial blood carbon dioxide (PaCO2) significantly increased, and arterial blood pH and bicarbonate (HCO3−) significantly decreased at 12 h. Shunt fraction was significantly increased at 12 h. In the NAC-treated group all animals survived to 12 h (n = 8). There was significantly improved arterial blood oxygen saturation, HCO3− levels, and shunt fraction compared to those of the sulfur mustard controls. There were significantly fewer neutrophils and lower concentrations of protein in lavage compared to sulfur mustard controls. Discussion. NAC's mucolytic and antioxidant properties may be responsible for the beneficial effects seen, improving clinically relevant physiological indices affected by sulfur mustard exposure. Conclusion. Beneficial effects of nebulized NAC were apparent following inhaled sulfur mustard exposure. Further therapeutic benefit may result from a combination therapy approach.